Traditional, complementary, and alternative medicine and the provision of health care to internally displaced persons in South Kivu, Democratic Republic of the Congo - Kazamwali, Muzee; Kisanga, Arsène; Balegamire, Juvenal B.; Kaningini, Euphrasie; Falisse, Jean-Benoît; Furaha, Germaine; Mapendo, Denise M.; Boeyink, Clayton (Frontiers in Human Dynamics, 2024)
Introduction Traditional, complementary and alternative medicine (TCAM) providers are central for many when seeking healthcare. Internally Displaced Persons (IDPs) are no exception. This paper seeks to better understand the use of TCAM by IDPs and its connection with the local integration of IDPs into the social fabric of the communities where they have taken refuge. We compare IDPs and non-IDPs access to TCAM providers and their level of confidence in having their healthcare needs met by these sources in Uvira and Kabare territories of South Kivu, Democratic Republic of Congo (DRC). Methods We draw from a mixed method, social connections design comprised of participatory workshops with 111 participants; a survey with 847 participants capturing exploring access and trust of TCAM and other wealth and demographic indicators; 24 interviews with traditional healthcare providers; and 56 in-depth life history interviews with IDPs. Collected data were analysed using both qualitative and quantitative approaches. Descriptive statistics (mean, percentage, and standard deviation) and statistical tests (proportions test and t test) were used as quantitative analysis tools whereas thematic content analysis was used for qualitative data. Results We show that IDPs use TCAM more than non IDPs. Access to and trust in traditional healers seems dependent on the exact nature of the services they offer, which varies across our sample. As such, processes of recognition and integration of both IDPs and TCAM providers into formal healthcare systems should be treated cautiously with an understanding of the socio-economic rationales that displaced people and TCAM providers operate under. While many of these TCAM providers are not highly trusted sources in South Kivu, their highly valued treatment of certain conditions such as what is locally known as “mulonge” (and bears similarities with the Buruli ulcer) suggest there may be potential specific areas where collaboration could be successful between biomedical health workers and TCAM providers.